Catatan dari Lereng Ile Boleng: Mengenali Lingkungan sebagai Landasan Pemberdayaan Pendidikan Dasar: Notes from the Valley of Ile Boleng: Identifying the Neighborhood as the Basis of Elementary Level Empowerment - Ilmi, Khintsiya Nadiatul (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2025)
Today, there have been many empowerment programs are aiming to increase economic level of rural communities. Related programs often experience discontinuity regarding to meet the expectation of quick changes instead of considering the community circumstances. Empowerment is not limited to economic values only. Transmission of knowledge, preservation, and advancement of culture are also the form of empowerment. This study focuses on empowerment programs to explore knowledge and ability of elementary school students of SDK Gayak Filial Nobo related to recognizing and understanding their surrounding environment in Nobo Village, Adonara, East Nusa Tenggara. The purpose of this empowerment research is to inventory, identify, and documenting local knowledge through a visual capture and written form. Through participation action research approach (PAR), students as research participants along with researcher as facilitator carry out the visual documentation elicitation method which is then narrated in three languages: local language, Indonesian, and English. As a result, using the approach and method show students' ability to identify and narrate objects that have been captured through visual documentation. Learning activities became fun, yet research participants became more sensitive to their surrounding environment.